THE STABILIZING OF ANATASE AEROGEL AT HIGH TEMPERATURE - Silvester Tursiloadi; Hiroshi Hirashima (Indonesian Journal of Chemistry, 2004)
Stable anatase is attractive to its notable functions for photo catalysis and photon-electron transfer.   Stable anatase TiO2 containing amorphous SiO2 aerogel was prepared by hydrolysis of Ti (OC3H7)4 and Si (OC3H7)4 in a 2-propanol solution with acid catalyst. The solvent in wet gels was supercritically extracted in CO2 at 60 oC and 22 Mpa. Thermal evolutions of the microstructure of the gels were evaluated by TGA-DTA, N2 adsorption and XRD. A stable anatase TiO2 containing amorphous SiO2 aerogel with a BET specific surface area of 365 m2/g and a total pore volume of 0.20 cm3/g was obtained as prepared condition. The anatase phase was stable after calcination up to 1000 oC, and BET specific surface area, total pore volume and average pore diameter did not change significantly after calcination up to 900 oC.